1990
DOI: 10.1139/b90-087
|View full text |Cite
|
Sign up to set email alerts
|

Widespread incidence of double-stranded RNAs of unknown function in rust fungi

Abstract: Double-stranded (ds) RNAs were found to be present in 33 of 38 collections of rust fungi, representing 15 species from four genera. This finding suggests that dsRNAs occur commonly in rust fungi. Tests were undertaken to determine the role or phenotype associated with the presence of dsRNAs. Comparisons were made between strains of Puccinia sorghi (maize rust) that had different dsRNAs and two fully isogenic strains of Melampsora lini (flax rust), one with no dsRNA and one with at least 13 dsRNAs. It was concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Double‐stranded (ds) RNA molecules are apparently common in rust fungi, given that they have been found in most rust species investigated. For example, of 11 Puccinia species investigated, all but one contained multiple dsRNAs, with each species having a distinct pattern of bands when separated by agarose gel electrophoresis (Pryor et al ., 1990; for a review see Zhang et al ., 1994). In four of the Puccinia species it has been shown that all the dsRNAs are encapsidated in isometric virus‐like particles of 40 nm diameter composed of capsid polypeptides in the 72–96‐kDa size range (Dickinson and Pryor, 1989a; Zhang et al ., 1994).…”
Section: Double‐stranded Rna Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Double‐stranded (ds) RNA molecules are apparently common in rust fungi, given that they have been found in most rust species investigated. For example, of 11 Puccinia species investigated, all but one contained multiple dsRNAs, with each species having a distinct pattern of bands when separated by agarose gel electrophoresis (Pryor et al ., 1990; for a review see Zhang et al ., 1994). In four of the Puccinia species it has been shown that all the dsRNAs are encapsidated in isometric virus‐like particles of 40 nm diameter composed of capsid polypeptides in the 72–96‐kDa size range (Dickinson and Pryor, 1989a; Zhang et al ., 1994).…”
Section: Double‐stranded Rna Moleculesmentioning
confidence: 99%
“…No phenotype has yet been associated with the dsRNAs in flax rust. For instance, the two isogenic strains LMS (no dsRNAs) and LMS‐SP6 (the isolate that contains all 11 dsRNAs in strain I) have identical patterns of virulence over a range of some 28 differential host lines and are indistinguishable in growth rate or in measured accumulation of fungal cell wall material during rust infection in the leaf (Pryor et al ., 1990). In addition, there was no evidence that LMS‐SP6 produces an allelopathic toxin that is transmitted to host cells surrounding the infection site, as LMS‐SP6 (+ dsRNAs) spores were not dominant when placed in close association (1–2 spore diameters) with LMS (no dsRNAs) spores on a leaf.…”
Section: Double‐stranded Rna Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have been associated with disease of Ophiostoma ulmi [4], increases and decreases in pathogen virulence in Phytophthora infestans [5], Rhizoctonia solani [6,7] and Cryphonectria parasitica [8], and allelopathic toxin production in Ustilago maydis [9]. DsRNAs occur in most strains of rust including the major pathogenic rust races of cereal crops [10,11]. There is no information available as to the function in rust fungi.…”
mentioning
confidence: 99%